Perspektif Hukum Islam Tentang Pembelian Barang Dengan Penambahan Harga Di Atas Harga Kontan (Studi Kasus Di Desa Buni Bakti Babelan Bekasi) - Munir, Ridwan; Azra, Luay busyairi (STAI Al Musaddadiyah Garut, 2023)
Buying and selling is an activity of exchanging goods for property in the form of money. There are several types of buying and selling in practice, namely cash buying and selling and not buying and selling (credit). Cash buying and selling is done in cash where payment is made in cash and completed in one transaction. Meanwhile, buying and selling credit payments are made in installments within a certain time. The problems examined in this study are: 1) How is the implementation of credit pricing of goods by traders, 2) How is the implementation of credit for household appliances and electronic devices in Buni Bakti Babelan Bekasi village, 3) How is the law of buying and selling credit with price additions according to Islam. The objectives of the study are: 1) To find out how the implementation of credit pricing of goods by traders, 2) To find out the implementation of credit for household appliances and electronic devices in Buni Bakti Babelan Bekasi village, 3) To find out the law of buying and selling credit with price additions according to Islam. The author uses field research methods using a qualitative approach. The data collection techniques used are observation, interviews, questionnaires, literature. Based on the results of the study, it can be concluded that the implementation of the pricing of goods carried out by traders depends on the type of goods taken by the buyers. The price increase in Islamic law is that Islam views the increase in price in the purchase of goods is first determined by the seller and buyer. Keywords: Islamic law, cash price, price addition;